The Pilgrimage to The San Nicola Shrine in Bari and its Impact - Rizzello, Katia (The international journal of religious tourism and pilgrimage, 2013)
Pilgrimage is defined as a journey to the Holy but more specifically as an inner journey to one's deepest religious feelings. This type of journey has assumed new forms and types that bring it closer to modern tourism in general, though it maintains its distinctive characteristics, which will be the object of this paper. These changes in the nature of pilgrimage, which in part reflect the parallel socio-cultural transformation of the average visitor, have brought about a major reorganisation of the places involved and have had a significant socio-economic impact on the territories involved. The concentration of visitors and in some cases the presence of various categories of visit have led to structural changes in holy places and their surroundings. These changes, which arise from the need to meet the requirements of travellers as consumers, in turn have social and environmental impacts on the surrounding area that are similar to those caused by mass tourism. The most evident types of impact are structural, resulting from the creation or expansion of hotel and catering infrastructure and the start-up of new businesses such as travel agencies, specialised tour operators, shops selling religious souvenirs and establishments providing entertainment. All this alters the physiognomy and the layout of the towns where the religious sites are located, in some cases completely transforming the economy of the location and the use of land. The aim of this research is to study pilgrimage flows associated with the cult of Saint Nicholas (San Nicola) in Bari, specifically concerning the pilgrimage's main characteristics and the most significant impacts on the district. The study follows a mixed approach that includes participant observation, use of archival documents and empirical evaluation of the material landscape and observed practices.[1]